A study of risk factors for infection with HPAI H5N1 in small poultry farms in Thailand using a questionnaire survey. - Siengsanan-Lamont, J; Robertson, I; Blacksell, S; Ellis, T; Saengchoowong, S; Suwanpukdee, S; Yongyuttawichai, P; Cheewajorn, K; Jangjaras, J; Chaichoun, K; Wiriyarat, W; Ratanakorn, P (2013)
A questionnaire was used to collect data on small poultry farm management and wild bird observed in poultry keeping areas to identify putative risk factors for infection with HPAI H5N1. The study was conducted in 2008 in four subdistricts of central Thailand that had experienced outbreaks of HPAI H5N1 in poultry. Descriptive and inferential analyses including univariable analyses and multivariable logistic regression were used to identify putative risk factors. Risk factors included purchasing native chickens/fighting cocks from commercial hatcheries, replacing or restocking birds individually, and observing lesser whistling ducks (Dendrocygna javanica) on the farm daily. Selecting healthy animals when purchasing animals to ensure that they were disease free was a protective factor. To fully understand the epidemiology of infection of small poultry farms with HPAI H5N1, control of movement of domestic poultry and serological and virological testing of the poultry population should be applied.